A chemically assisted ignition mathematical model based on the theory of thermal ignition. (July 2022) - Jiao, Aihong; Huang, Ping; Qian, Xinming; Feng, Changgen; Liu, Zhenyi
Abstract: A chemical ignition mathematical model was established based on the analysis of the process of chemical ignition and thermal ignition theory . Then, the model was solved by the method of nets on a computer to explore the mechanism for in-situ combustion ignition with chemical additives. Also, the development course of in-situ combustion ignition was reviewed. In addition, the ignition process by chemical methods was analysed. It was shown that the mathematical model was able to calculate some parameters such as the critical duration of the outer source action and critical energy for ignition. The heat flux that ignites an oil layer is greater than 2.35, when its dimensionless initial activation energy ɛ and initial temperature θ 0 are 0.026 and 11. Moreover, the ignition process and temperature distribution of oil sands were described with the model. The results are of great theoretical significance for understanding chemically assisted ignition mechanism in-depth, controlling ignition parameters and guiding chemical additives formulation design and optimization, etc.